Peran Orang Tua dalam Mengajar untuk Meningkatkan Pengalaman Belajar Anak Usia Dini - Mutakim, Jaenal; Komar, Oong; Sudiapermana, Elih; Pramudia, Joni Rahmat; Herawaty, Henny; Nuraeni, Lenny (Jayapangus Press, 2025)
Introduction of children to formal education environments outside the home requires collaboration between teachers, parents, and schools. Family-school partnerships are key to creating a learning environment that supports early childhood development. This study aims to explore the implementation of the Parents as Teachers program in building effective partnerships between teachers and parents, analyze its impact on children's learning experiences, and evaluate the role of the school committee as a primary facilitator in program implementation. This study employed a qualitative method with a case study approach. Data were collected through direct observation, in-depth interviews with various stakeholders, and document analysis related to program implementation at an early childhood education school in Jakarta. The findings indicate that involving parents as learning resource persons not only provides students with authentic learning experiences but also strengthens communication between teachers and families. Teachers utilize discussions with parents to gain a deeper understanding of student characteristics, enabling the design of more relevant and contextual learning. The program successfully created an educational ecosystem that actively involves multiple stakeholders, with the school committee serving as a key supporter of the program's sustainability. Through this approach, family-school collaboration becomes more harmonious, positively impacting students' holistic development. This program demonstrates the importance of synergy among all stakeholders in fostering inclusive and sustainable education.